Epigenetic memory as crucial contributing factor in directing the differentiation of human iPSC into pancreatic β-cells in vitro - Abdoulaye Diane (14152749) (2025)
Impaired insulin secretion contributes to the pathogenesis of type 1 diabetes mellitus through autoimmune destruction of pancreatic β-cells and the pathogenesis of severe forms of type 2 diabetes mellitus through β-cell dedifferentiation and other mechanisms. Replenishment of malfunctioning β-cells via islet transplantation has the potential to induce long-term glycemic control in the body. However, this treatment option cannot widely be implemented in clinical due to healthy islet donor shortage. Emerging β-cell replacement with human-induced pluripotent stem cell (iPSC) provides high remedial therapy hopes. Thus, tremendous progress has been made in developing β-cell differentiation protocols in vitro; however, most of the differentiated iPSC-derived β-cells showed immature phenotypes associated with low efficiency depending on the iPSC lines used, creating a crucial barrier for their clinical implementation. Multiple mechanisms including differences in genetic, cell cycle patterns, and mitochondrial dysfunction underlie the defective differentiation propensity of iPSC into insulin-producing β-cells. Accumulating evidence recently indicated that, following the reprogramming, epigenetic memory inherited from parental cells substantially affects the differentiation capacity of many iPSC lines. Therefore, differences in epigenetic signature are likely to be essential contributing factors influencing the propensity of iPSC differentiation. In this review, we will document the impact of the epigenome on the reprogramming efficacy and differentiation potential of iPSCs and how targeting the epigenetic residual memory could be an additional strategy to improve the differentiation efficiency of existing protocols to generate fully functional hPSC-derived pancreatic β-cells for diabetes therapy and drug screening. Other Information Published in: Cell and Tissue Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00441-025-03952-8